PENDAMPINGAN DAN PENGUATAN KARAKTER GENERASI MUDA MELALUI SINERGI BUILDING DAN ENTREPRENEURSHIP PROGRAM PADA SMA PGRI PURWOHARJO BANYUWANGI - Rizqi, Maulidyah Amalina; Uli Nuha, Sukma (Universitas Muhammadiyah Gresik, 2024)
Community service activities held at SMA PGRI Purwoharjo Banyuwangi aim to provide creativity, innovation, intelligence and skills that can benefit the environment around them. As a young generation with character, they must be able to have a strong mentality in dealing wih various problems that occur in society. Synergy between youth and society is an important aspect in realizing changes in the environment around them towards a better and more advanced direction. The method used in this service is to provide training and mentoring to get maximum results. Some of the training that will be providedis the Leadership Training Program, Team Building Program, Character Building Program, and Entrepreneurship Training. The results of the training and mentoring show an increase in participants understanding of the importance of strengtjening character for the younger generation through synergy building and entepreneurship programs. The service team also provides several entrepreneurial program / activities that can be carried out by students at SMA PGRI Purwoharjo Banyuwangi.